Odpowiedzi

2009-11-25T11:24:07+01:00
1(3- pier. z 3)=3- pier. z 3
(3+ pier. z 3)(3- pier. z 3)=9-3

5(pier. z 5 +3)=5pierw. z 5 +15
(pier. z 5 -3)(pier. z 5 +3)=25-9
2009-11-25T11:43:15+01:00
1
---------=mnożymy licznik i mianownik przez 3-√3
3+√3

1(3-√3)
=--------------- =
(3+√3)(3-√3)

3-√3
=-----------------------
9-3

3-√3
=---------------
6
b)

5
-------=
√5-3


5( √5-3 )
----------------=
( √5-3 )( √5+3 )

5√5-15
-------------=
5-9

5√5-15
-------------
-4
2009-11-25T13:59:25+01:00
1
---------=mnożymy licznik i mianownik przez 3-√3
3+√3

1(3-√3)
=--------------- =
(3+√3)(3-√3)

3-√3
=-----------------------
9-3

3-√3
=---------------
6
b)

5
-------=
√5-3


5( √5-3 )
----------------=
( √5-3 )( √5+3 )

5√5-15
-------------=
5-9

5√5-15
-------------
-4